PENGARUH PEMBELAJARAN AQIDAH AKHLAK TERHADAP PERILAKU SISWA DI MADRASAH ALIYAH NEGERI KAMPAR TIMUR - Yanti, Siska Fitri; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study consisted of two variables, namely learning morals aqidah (variable X) on behavior (ethics, manners and morals) students (variable Y). This study aims to determine the effect on behavior of learning aqidah morals (ethics, manners and morals) students in Madrasah Aliyah East Kampar. While the problem is there any influence aqidah learning morals on behavior (ethics, manners and morals) students in Madrasah Aliyah Negeri East Kampar. This research subject and object is XII class is learning aqidah morals. The population is all students of class XII, because its population is less than 100 then the sample is all population of 75 people. Data collection methods that I use is observation, questionnaires and dokumantasion, to analyze the data, the author uses descriptive quantitative presented in tabular form and then described in detail later in the analysis with a simple linear regression, based on the results and analysis of data. The existence of significant influence between learning aqidah character of the behavior student in Madrasah Aliyah Kampar country east. Keywords: Learning, Aqidah Morals, Conduct (ethics, manners and morals)